Numerical modelling of multi-pass solar dryer filled with granite pebbles for thermal storage enhancement - Kareem, M.W. (Institute of Physics Publishing, 2015)
In this paper, a theoretical modelling of a cheap solar thermal dryer for small and medium scale farmers with multi-pass approach has been investigated. Comsol Multiphysics modelling tool was employed using numerical technique. The rock particles were used to enhance the thermal storage of the drying system. The local weather data were used during the simulation while parameters and coefficients were sourced from literature. An improvement on efficiency of up to 7 was recorded with error of 10-5 when compared with the reported double pass solar collector. A fair distribution of hot air within the cabinets was also achieved. Though the modelling tool used was robust but the characterization of the system materials need to be done to improve the system accuracy and better prediction.